Thermoeconomic assessment of an adsorption cooling/desalination cycle coupled with a water-heated humidification-dehumidification desalination unit. (1st November 2020) - Elbassoussi, Muhammad H.; Mohammed, Ramy H.; Zubair, Syed M.
Highlights: Coupled Adsorption and humidification-dehumidification technologies are investigated. The coupled system has the capability of producing both cooling capacity and freshwater. A thermoeconomic model for the system is developed to explore the system features. The cost of freshwater produced is estimated at around 1.15 ȼ/liter, while the GOR is 2.50. Considerable saving in the freshwater cost (between 30% and 40%) is attained. Abstract: Adsorption desalination (AD) and humidification-dehumidification desalination (HDH) technologies are attractive since they can be powered by low-grade energy sources and can be constructed on a small scale. This paper adopts a novel hybrid AD-(water-heated) HDH system to produce freshwater and cooling power, simultaneously. The system is mainly powered by a low-grade energy source (natural gas), while photovoltaic (PV) panels are used to run the auxiliary components such as pumps, and blowers. A detailed thermoeconomic model is developed to explore the effect of different parameters on the system performance and products' cost. This analysis reveals that the system can deliver, at its optimal operating conditions, 21.75 kg of freshwater per hour for 1.15 ȼ/liter with a gained output ratio (GOR) of 2.50. The coefficient of performance (COP) and the cooling capacity of the proposed system are recorded at 0.46 and 2.53 kW, respectively. Besides, a comparison between the proposed hybrid system and a traditional standalone water-heated HDH unit is performed. This comparison shows that the GOR value of the hybrid system is always higher than that of the standalone HDH (about 350% increase). This trend indicates that the proposed system significantly improves overall performance. Considerable saving in the freshwater cost (from 30 to 40%) is also attained.